2016
DOI: 10.1002/mnfr.201600230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n‐3 fatty acid supplements on glycemic traits in Chinese type 2 diabetic patients: A double‐blind randomized controlled trial

Abstract: Marine n-3 PUFA supplements may improve glycemic control and lipid profiles among Chinese type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 38 publications
1
45
2
2
Order By: Relevance
“…We conducted a multi-centre double-blind parallel randomised controlled trial (n = 185) to investigated the effects of n-3 PUFA supplements (both marine [fish oil] and plant source [flaxseed oil]) on glycaemic traits in Chinese patients with T2D. This trial found that fish oil supplement, compared with corn oil control group, significantly decreased glycated hemoglobin (HbA1c) and TG 18 . In the present study, using serum metabolomics data (n = 53) from a single centre of the aforementioned multi-centre trial ( Fig.…”
mentioning
confidence: 99%
“…We conducted a multi-centre double-blind parallel randomised controlled trial (n = 185) to investigated the effects of n-3 PUFA supplements (both marine [fish oil] and plant source [flaxseed oil]) on glycaemic traits in Chinese patients with T2D. This trial found that fish oil supplement, compared with corn oil control group, significantly decreased glycated hemoglobin (HbA1c) and TG 18 . In the present study, using serum metabolomics data (n = 53) from a single centre of the aforementioned multi-centre trial ( Fig.…”
mentioning
confidence: 99%
“…Furthermore, a 12-week flaxseed oil supplementation was effective in improving insulin levels, HOMA-IR and QUICKI in patients with diabetic foot ulcer (13) . However, flaxseed oil supplementation (2•5 g/d) for 6 months did not improve glycaemic control and lipid profiles in patients with T2DM (14) . In another study, 6-week vitamin D supplementation had no significant effect on glycaemic control and lipid profiles in overweight and obese women (39) .…”
Section: Effects On Glycaemic Control and Lipid Profilesmentioning
confidence: 82%
“…Previously, we observed that flaxseed oil supplementation significantly reduced insulin resistance in patients with diabetic foot ulcer (13) . However, in another study, it did not show any beneficial effect on glycaemic control and lipid profiles in diabetic patients (14) . Flaxseed oil contains essential fatty acid that may inhibit the production of inflammatory markers (15) and affect mRNA expression of transcription factors involved in the metabolic pathways (16) .…”
mentioning
confidence: 88%
“…The inclusion and exclusion criteria, and the detailed procedures of the trial has previous been reported [ 14 ]. Briefly, the inclusion criteria were fasting blood glucose>7.0 mmol/L or on use of diabetic medications, participants between 35 and 80 years for men or between postmenopausal and 80 years for women; the exclusion criteria were having familial hyperlipidemia or with blood triglycerides >4.56 mmol/L, having a history of hepatic or kidney disease or any type of cancer, or participation in another clinical trial within 30 days prior to screening.…”
Section: Methodsmentioning
confidence: 99%